Nintendo Wii Fit-Based Sleepiness Testing is Not Impaired by Contagious Sleepiness - Aino Tietäväinen; Maria Kuvaldina; Edward Hæggström (Elsevier, 2018)
Sleep deprivation may cause accidents, and it has deteriorating effects on health. A measurement of postural steadiness by a portable and affordable Nintendo Wii Fit balance board can be used to quantify a person's alertness. At work, people are under the influence of their environment-often other people-that may affect their alertness. This work investigates whether sleep deprivation among people is "contagious," as quantified by sway measures. We measured 21 volunteers' postural steadiness while alert and sleep deprived. During the measurements, a screen placed in front of the participants showed a footage of either alert or sleep-deprived faces. We found a significant difference between the day time and night time steadiness, but found no effect resulting from watching footage of sleep-deprived people. This finding shows that a posturographic sleepiness tester quantifies physiological sleep deprivation, and is insensitive to the influence of social factors. Keywords: contagious sleepiness, portable and affordable sleepiness tester, posturography, social contagion